2011
DOI: 10.1002/pmic.201100189
|View full text |Cite
|
Sign up to set email alerts
|

QSE: A new 3‐D solvent exposure measure for the analysis of protein structure

Abstract: Solvent exposure of amino acids measures how deep residues are buried in tertiary structure of proteins, and hence it provides important information for analyzing and predicting protein structure and functions. Existing methods of calculating solvent exposure such as accessible surface area, relative accessible surface area, residue depth, contact number, and half-sphere exposure still have some limitations. In this article, we propose a novel solvent exposure measure named quadrant-sphere exposure (QSE) based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Bioinformatics studies over the past few decades have shed light on topics such as sequence analysis, structural analysis, and network and systems biology [ 1 , 2 ]. In recent years, rapid improvements in technology and decreased sequencing costs have made next-generation sequencing possible, facilitating millions of short sequence reads that have broad genomic research applications [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics studies over the past few decades have shed light on topics such as sequence analysis, structural analysis, and network and systems biology [ 1 , 2 ]. In recent years, rapid improvements in technology and decreased sequencing costs have made next-generation sequencing possible, facilitating millions of short sequence reads that have broad genomic research applications [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The imprecision and uncertainty in measurement of the SEA of amino acid residues accordingly inspire the employment of fuzzy logic to characterize amino acids in PSSP. As numerous studies have found the significance of the amino acid SEA in understanding protein structures and functions [26][27][28], utilizing the SEA therefore would enhance the predictability of the protein secondary structure. In this paper, triples representing SEA of amino acids are employed as part of the amino acid representation.…”
Section: ) Solvent Exposed Area (Sea) Of Amino Acids (å 2 )mentioning
confidence: 99%
“…Raw data in the form of 3d chain antigen structures containing information on residues exposed at the atomic level and labeled epitope and non-epitope was taken from Gao et al [7]. These residues are enriched with features of structural analysis with PSAIA, which include ASA, RSA, and Protrusion Index [26], Contact Number [27], QSE [28], HSE [29], AAIndex [30], B Factor [31] and Log Odd Ratio [32]. The dimension of the vector properties is 601.…”
Section: Dataset Collectionmentioning
confidence: 99%